The impact of COVID-19 on the mental health of pregnant women in Shanghai, China - Zhang, Jiali; Yuan, Hualong; Xu, Liping; Yi, Chuntao; Tang, Weiming (Frontiers in Public Health, 2022)
Background: COVID-19 has dramatically impacted people's health, especially mental health. This study aimed to compare the psychological status of pregnant women before and after the COVID-19 outbreak. Method: Participants were recruited (from September 29, 2019, to November 5, 2020) and screened by the Patient Health Questionnaire (PHQ-9) and the Generalized Anxiety Disorder Scale (GAD-7). The study participants were categorized into three groups based on two turning-point: January 23, 2020, when China initiated a locked-down strategy, and May 11, 2020, when Shanghai started to ease the COVID-19 measures. Multivariable logistic regression was used to determine the factors associated with depression and anxiety in pregnant women. We used enter method for variable selection; only variables with P<0.10 were included in the final model. Results: We recruited 478 pregnant women. After the outbreak, the depression rate (PHQ-9≥5) increased by 12.3% (from 35.4% to 47.7%), and the anxiety rate (GAD-7≥5) was stable (13.3% VS 16.2%). The multivariable logistic regression results further confirmed that the odds of depression in pregnant women increased 81% after the outbreak (aOR=1.81, 95%CI: 1.16-2.84). However, the median depression scale score was still statistically higher after the pandemic situation was stable (5.0 vs. 4.0) compared to the outbreak period. Conclusion: The depression rate increased among pregnant women after the outbreak and was not recovered after the ease of COVID-19 measures in Shanghai. Health institutes should pay attention to the long-term influence of the pandemic.